2007
DOI: 10.1007/s00508-007-0809-0
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular reactivity is impaired in patients with non-insulin-dependent diabetes mellitus and microangiopathy

Abstract: CVR is impaired in normotensive NIDDM patients. These cerebral hemodynamic changes correlate significantly with the duration of DM, parameters of inflammation, proteinuria and serum creatinine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…Among demographic factors examined in our study (sex, age and weight) and underlying diseases (DM and hypertension), only DM was found to be a significant covariate, decreasing the slope related to the reactivity of rSO 2 in response to changes in EtCO 2 , which is consistent with the previous result that Type 2 DM is associated with impaired cerebrovascular reactivity to PaCO 2 compared to healthy agematched controls [15][16][17]. It has been reported that one reason for reduced cerebrovascular reactivity in patients with DM is endothelial dysfunction caused by an imbalance between endothelium-derived vasodilator and vasoconstrictor substances [25].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Among demographic factors examined in our study (sex, age and weight) and underlying diseases (DM and hypertension), only DM was found to be a significant covariate, decreasing the slope related to the reactivity of rSO 2 in response to changes in EtCO 2 , which is consistent with the previous result that Type 2 DM is associated with impaired cerebrovascular reactivity to PaCO 2 compared to healthy agematched controls [15][16][17]. It has been reported that one reason for reduced cerebrovascular reactivity in patients with DM is endothelial dysfunction caused by an imbalance between endothelium-derived vasodilator and vasoconstrictor substances [25].…”
Section: Discussionsupporting
confidence: 81%
“…Meanwhile, changing partial pressure of carbon dioxide in arterial blood (PaCO 2 ) is the strongest modulator of CBF because a linear relationship exists between PaCO 2 and CBF within a normal physiological range of PaCO 2 (20-75 mmHg) [12]. However, when considering cerebrovascular reactivity to PaCO 2 , other factors such as MAP, use of anaesthetic agents and disease states should be taken into account [12][13][14][15][16][17][18][19].In practice, cerebrovascular reactivity to PaCO 2 can be assessed by measuring cerebral oxygen saturation (rSO 2 ) with a near-infrared spectroscopy device [20], which has been used as a non-invasive and continuous monitoring method for detecting cerebral ischaemia in various clinical situations [8]. It measures the ratio of oxygenated haemoglobin and deoxygenated haemoglobin, and rSO 2 values are calculated based on the assumption of a fixed reference ratio of 25% arterial and 75% venous contribution [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ECD and TCD ultrasound, by utilizing the PI and RI, proved a reliable tool in the assessment of structural and functional changes in the cerebral vessels in asymptomatic non-diabetic and diabetic CKD patients, modifications which correlated with classic and non-classic cerebrovascular risk factors [17][18][19][20][21][22].…”
Section: Cerebral Vessels Modificationsmentioning
confidence: 99%
“…1,2 Endothelial dysfunction precedes the development of clinically evident vascular complications 3,4 and in many vascular beds has been shown to be proportional to the severity of DM or IR. 5,6 Endothelial function can be assessed by quantifying the vascular reactivity (VR) of any vascular bed in response to a stimulus.…”
Section: Introductionmentioning
confidence: 99%